Application of New Technical Decisions in the Industrial Flax Production - Berezovsky, Yu.V. (Science and Innovation, 2024)
The use of flax and flax-containing products in the economy and increase in its output require modifying the qualitative and quantitative properties of the flax fiber. The research concerns the features of the effects of timber and other nonfibrous impurities of stem material on the fiber integrity during deformation of plant stems in the flax processing. The modifications in the process equipment for bast raw material processing have been showed to effect the results of stem material treatment, especially, the degree of purity of the obtained fibrous product.